The Bologna Process: meaning, aims and controverse - Luzón Trujillo, Antonio; Sevilla Merino, Diego; Torres Sánchez, Mónica (Avances en Supervisión Educativa, 2009)
One might ask why we must work for the creation of a European Space of Higher Education. Must we consider if we have got the right or the duty to oppose it or support it? It is not possible to assume unconsciously a process such as the Bologna Process, nor to ignore the consequences that our stance will cause. This article tries to find its sense and offer a series of items to facilitate the understanding of its meaning and the suitability of the creation of the European Space of Higher Education.